Learning analytics beyond the LMS : enabling connected learning via open source analytics in 'the wild' : final report. - Kitto, Kirsty; Lupton, Mandy; Bruza, Peter; Mallett, Dann; Banks, John; Dawson, Shane; Gasevic, Dragan; Buckingham Shum, Simon; Pardo, Abelardo; Siemens, George (Australia. Dept of Education, Skills and Employment, 2020)
Over the past decade we have witnessed a proliferation of new technologies involving an increasingly sophisticated use of data. In education, the field of learning analytics (LA) is one such example, seeking to explore how the analysis of student data can bring new insights into the learning process. However, the breadth and diversity of technologies available today and the corresponding wealth of learning data stands in stark contrast to the day-to-day operations and processes that operate in formal education. Large educational systems such as universities, TAFEs and other providers have an essential requirement for technical stability and scalability. The learning management system (LMS) is an example of a standalone solution that provides stability and scalability. LMSs combine myriad features that can be used in learning and teaching. From the management of courses and enrolment, to discussions, group work, and even assessment and assignment tracking, the modern day LMS provides a seemingly viable solution. This project explored the dynamic between the need for teaching innovation alongside the need for the formal administration of education technologies. The Beyond LMS project aimed to improve the quality of student engagement and learning in collaborative online environments by incorporating analytics developed using the data generated in social media platforms that the majority of students already use. [Executive summary, ed]